2021
DOI: 10.1002/anie.202107955
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Gas–Solid Treatment for Surface Modification of Li‐Rich Oxides Cathodes

Abstract: Li-richl ayered oxides with high capacity are expected to be the next generation of cathode materials. However,t he irreversible and sluggish anionic redox reaction leads to the O 2 loss in the surface as well as the capacity and voltage fading.I nt he present study,asimple gas-solid treatment with ferrous oxalate has been proposed to uniformly coat at hin spinel phase layer with oxygen vacancy and simultaneously realize Fe-ion substitution in the surface.T he integration of oxygen vacancy and spinel phase sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 61 publications
(14 reference statements)
0
60
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29] Oxygen vacancies have been proved to inhibit voltage decay and lattice oxygen escape in some studies. [30,31] Nakamura et al found that the oxygen-deficient materials exhibited a greater hysteresis voltage than the bare sample due to a facilitated cation migration. [30] But the underlying mechanism still needs to be further clarified.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Oxygen vacancies have been proved to inhibit voltage decay and lattice oxygen escape in some studies. [30,31] Nakamura et al found that the oxygen-deficient materials exhibited a greater hysteresis voltage than the bare sample due to a facilitated cation migration. [30] But the underlying mechanism still needs to be further clarified.…”
mentioning
confidence: 99%
“…It can be seen that the surface O 1s spectrum can be roughly divided into three peaks, 529, 531, and 533 eV, attributed to O 2− lattice oxygen in MO 6 , partially oxidized per‐oxygen species O n − (0 < n < 2), and carbonate deposition species CO 3 2− on the surface, respectively. [ 34,43,48 ] Prominently, the O 1s spectrum of SLNMO can hardly separate the peak of oxidized sedimentary species on surfaces, and the O n − content has almost doubled compared with LNMO, affirming that SLNMO has stronger oxygen anion redox activity. After charging to 4.8 V, compared to LNMO, SLNMO still has less surface deposition and more per‐oxygen species O n − .…”
Section: Resultsmentioning
confidence: 99%
“…The broadened and low intensity peaks located at a range of 20–25° are characteristic of the monoclinic Li 2 MnO 3 ‐like component ( C 2/ m ) owing to the lithium‐cation ordering in the transition‐metal layers [14] . The well spilt peaks of (006)/(102) and (108)/(110) illustrate the high order of the hexagonal structure [15] …”
Section: Figurementioning
confidence: 98%